2007
DOI: 10.1016/j.compfluid.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Time-accurate computations of isolated circular synthetic jets in crossflow

Abstract: Results from unsteady Reynolds-averaged Navier-Stokes computations are described for two different synthetic jet flows issuing into a turbulent boundary layer crossflow through a circular orifice. In one case the jet effect is mostly contained within the boundary layer, while in the other case the jet effect extends beyond the boundary layer edge. Both cases have momentum flux ratios less than 2. Several numerical parameters are investigated, and some lessons learned regarding the CFD methods for computing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…URANS was particularly unsuccessful at predicting turbulence quantities. A later publication by Rumsey et al 33 contrasted case 3 with a similar synthetic jet experiment conducted at NASA Glenn Research Center. It was emphasized that there were differences between case 2 PIV and LDV measurements in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions.…”
Section: B Urans Methodsmentioning
confidence: 99%
“…URANS was particularly unsuccessful at predicting turbulence quantities. A later publication by Rumsey et al 33 contrasted case 3 with a similar synthetic jet experiment conducted at NASA Glenn Research Center. It was emphasized that there were differences between case 2 PIV and LDV measurements in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions.…”
Section: B Urans Methodsmentioning
confidence: 99%
“…Rumsey reported that unsteady RANS (URANS) was particularly unsuccessful to predict turbulence quantities. Rumsey et al emphasized that there were differences between particle image velocimetry (PIV) and laser Doppler velocimetry (LDV) measurements of the current case in some regions of the flow, and the URANS computations tended to agree better with the LDV data in those regions. In confirmation, all turbulence models by the coarse grid of Rumsey in a normal domain size can capture the general character of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…3. Unsteady Reynolds-Averaged Navier-Stokes equations were solved using ANSYS CFX as described in [8,26]. The k-ω Shear Stress Transport turbulence model has been found to best simulate dynamic stall [10,23,29] as well as synthetic jet actuation in crossflows [30], and was consequently employed in this study.…”
Section: Methodsmentioning
confidence: 99%